An integrated Machine Learning Model for Manufacturing industry - Mulongo, Yves (AI Society & STMIK Indonesia, 2022)
The purpose of this article is to examine the process of developing services based on machine learning technologies in a manufacturing environment context. Over the past decade, there has been a resurgence of interest in technology, with prominent technology business organisations and several start-ups incorporating it into their operations. The technology's widespread applications capacity for obtaining a competitive advantage, combined with the prospect of task automation for increased operational efficiency, renders it a significant resource for large corporations. Yet, the rate at which most of manufacturing firms are implementing Machine Learning services into their operations is very insignificant. Technical expertise has dominated study in this field, with minimal participation from other areas. Thus, the goal of this article is to identify the development benefits of Machine Learning services and to provide a process model for their deployment, based on service development and value theory.